MODELING AND RECOMPOSING KNOWLEDGE: THE USE OF HOMEMADE MODELING DOUGH AND STICKS IN TEACHING GEOMETRIC SOLIDS - Barbosa de Sena , Sidney; Barbosa de Sena , Enilda (Journal of Interdisciplinary Debates, 2025)
High school mathematics teaching faces challenges in addressing abstract content such as geometric solids, especially in state schools, where the scarcity of teaching resources and the need for contextualized methodologies exacerbate these difficulties. This paper reports on an experiment developed with first-year vocational high school students at CEEP Professor Francisco de Assis Pedrosa in Mossoró, Rio Grande do Norte. The experiment involved using three-dimensional modeling of geometric solids with homemade modeling clay and toothpicks, which can also be made to provide meaningful learning about geometric solids. The qualitative approach, based on participant observation, photographic records, and oral accounts from students, structured the teaching sequence in classes that interspersed theory and practice through the collective production, modeling, and assembly of geometric solid models to reconstruct this knowledge. The results indicated excellent student engagement, improved content comprehension, and strengthened collaborative work and critical thinking, in accordance with the BNCC guidelines (BRASIL, 2018). In short, the experience demonstrated that alternative teaching resources and active methodologies can expand learning possibilities and strengthen the connection between school, scientific knowledge, and students’ realities.